Motivation and academic performance in the students of the subject "Social Doctrine of the Church", Universidad Católica de Santa Maria - Miguel Oswaldo Chire Salazar (2019)
When investigating the influence of the motivation in the academic performance of the students ofthe subject "Social Doctrine of the Church" in the Professional Programs of Human Medicine, Civil Engineering, Accounting and Psychology, corresponding to the odd semester 2010 of the Universidad Católica de Santa María; was raised about the hypothesis that the significant differences that show the evaluations of the mentioned subject, owe to the influence of the intrinsic and extrinsic motivation of the students; hypothesiscorroborated with the application of the statistical techniques of Coefficient of Correlation of Pearson and Test Chi-square. The sample was conformed by 210 students of the subject object of study of the signal professional programs.The used sampling technique was the Non Probabilistic for Convenience, applied by means of surveys that contained a structured questionnaire created in unpublished form, as well as the record of registration of notes; being supplemented with documented information. The results but significant they indicate that most of the students of the programs professional investigation matter, they were motivated in the personal thing by the content of the subject "Social Doctrine of the Church". In the intrinsic motivation, the aspects that more they influenced they were the values and the religious identity; and in the extrinsic motivation, 1t highlighted the aspect of the social projection. Also, it was verified that the academic yield of most of students in the mentioned subject, was of Half Term.